The role of climate change adaptation of small-scale farmers on the households food security level in the west of Iran. Issue 5 (4th July 2021) - Savari, Moslem; Zhoolideh, Milad
ABSTRACT: Undoubtedly, among the priorities of development goals in each country, achieving sustainable food security and also adapting to climate change have special importance. Therefore, the present study was conducted to analyse the role of adaptation capability of small-scale farmers against climate change on the households' food security level in the west of Iran. The statistical population of the research included all small-scale farmers in the west of Iran, in Ilam, Kurdistan, and Kermanshah provinces ( N = 319618). By using Krejcie and Morgan Table, and stratified sampling, 404 people were selected with optimum allocation. The main data-gathering tool in the research was a questionnaire which its validity and reliability were confirmed by a group of experts and Cronbach's alpha coefficient, respectively. The results of this research show the poor situation of food security in rural households, and it also indicates their low adaptability against climate change. Also, the results of the discriminant analysis showed that five components of adaptation capability (financial, natural, human, social, and physical) could differentiate food secure groups with insecure ones with 95% accuracy.